2020
DOI: 10.1186/s12860-020-00301-1
|View full text |Cite
|
Sign up to set email alerts
|

An Endostatin-lentivirus (ES-LV)-EPC gene therapy agent for suppression of neovascularization in oxygen-induced retinopathy rat model

Abstract: Background: Transplantation of gene transfected endothelial progenitor cells (EPCs) has provided novel methods for tumor neovascularization therapy but not for ocular disease therapy. This study aimed to investigate the efficacy of endostatin transfected EPCs in retinal neovascularization therapy. Results: Quantitative reverse transcription-polymerase chain reaction (qRT-PCR) showed the high expression of endostatin in endostatin-lentivirus-EPCs. The neovascularization leakage area and the number of preretinal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…attenuated the level of NADPH oxidase activity and O2 .generation and decreased the number of OECs stained positive for SA--gal activity and DNA damage marker, -H2AX, by approximately 20% (Figure 5bg).Furthermore, both treatment regimens increased the cellular proliferation rate and tubulogenic activity coupled with increases in the number and length of tubules (Figure6ad). Considering the elevations observed in endostatin levels in both senescent OECs and older individuals alongside the previous studies attributing a crucial role to this anti-angiogenic factor in OEC functionality(Ai et al 2020), we also investigated the level of endostatin in cells treated with VAS2870 or vitamin C. In line with tubulogenic study data, suppression of oxidative stress effectively prevented senescence-evoked increases in endostatin levels (Figure6e). Finally, suppression of oxidative stress by either agent led to better integrations between senescent OECs and HBMECs and improved the tightness and functionality of cerebral barrier, as evidenced by increases in TEER and decreases in paracellular flux of NaF (Figure6f, g).…”
mentioning
confidence: 54%
“…attenuated the level of NADPH oxidase activity and O2 .generation and decreased the number of OECs stained positive for SA--gal activity and DNA damage marker, -H2AX, by approximately 20% (Figure 5bg).Furthermore, both treatment regimens increased the cellular proliferation rate and tubulogenic activity coupled with increases in the number and length of tubules (Figure6ad). Considering the elevations observed in endostatin levels in both senescent OECs and older individuals alongside the previous studies attributing a crucial role to this anti-angiogenic factor in OEC functionality(Ai et al 2020), we also investigated the level of endostatin in cells treated with VAS2870 or vitamin C. In line with tubulogenic study data, suppression of oxidative stress effectively prevented senescence-evoked increases in endostatin levels (Figure6e). Finally, suppression of oxidative stress by either agent led to better integrations between senescent OECs and HBMECs and improved the tightness and functionality of cerebral barrier, as evidenced by increases in TEER and decreases in paracellular flux of NaF (Figure6f, g).…”
mentioning
confidence: 54%
“…In the OIR mouse model, the RGD peptideconjugated dye (AF488-RGD 2 ) was able to selectively detect regions of high integrin α v β 3 expression, which were portions of the area where CD31 was expressed (Figure 2). CD31, which serves as a marker for vascular endothelial cells, is expressed in both normal blood vessels and neovascular areas of OIR mouse models, with higher levels of expression observed in OIR retinas [51,52]. In contrast, integrin α v β 3 is typically expressed in areas with neovascularization rather than in normal vessels, and its expression is significantly upregulated in the neovascular endothelial cells present in the retinas of OIR mice [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated endostatin levels in amniotic fluid have been shown to be correlated with the development of severe ROP in preterm infants [ 128 ] possibly highlighting its role in microvascular degeneration during phase 1 ROP. Some authors have shown that the retinal administration of endostatin is effective in preventing pathologic retinal neovascularization in an OIR model [ 162 ].…”
Section: Cytokines: Characteristics and Actionsmentioning
confidence: 99%